Pembuatan dan Pengujian Paket Modular untuk Speed Test Kapal pada Tahap Sea Trial - Kharismawan Dwi Febrianto; Budianto Budianto; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the performance tests that must be carried out by the ship before launch is the progressive speed test. In doing the required speed test GPS-based devices. In previous research has been designed a software sea trial tracker that is able to process data from GPS devices quickly and efficiently. This study aims to create a device that can be used to support sea trial tracker software and make it easier for testers to perform a performance test with a portable and efficient device design which is then expected to be widely used in the ship performance test process. The device manufacturing process is carried out starting from the design stage of the design with the help of CAD software, component planning, and the assembly stage. The device testing method will be done directly at the sea trial stage and the test results will be compared with the results of hullspeed analysis using maxsurf software to determine the success of device function. Based on the results of the creation and testing of a modular performance package, this device is able to be used to support the sea trial tracker software as evidenced by the speed test on the sea trial. Modular package that is made using a battery with a capacity of 12V 3.5Ah which is able to supply the power needs of the device for 4-9 hours of use and is equipped with a battery charger that is able to charge the battery from empty to full within 25 minutes. Comparison between the results of a modular package test and the results of the maxsurfhullspeed software analysis shows the results that meet the 10% validation limit that has been determined, so that the modular package is capable of being used in a ship speed test.